Tinjaun Pernikahan Dalam Masa Iddah Istri Terhadap Surat Edaran Dirjen Bimas Islam - Ali hamdan; burhanatutdyana; Refangga (Al Maqashidi : Jurnal Hukum Islam Nusantara, 2023)
This article examines the review of marriage after a circular issued by the Ministry of Religion regarding marriage during the wife's iddah period. In the circular there is a provision that the husband can remarry another woman if the wife's iddah period is over. If this is related to the provisions on the wife's iddah period, both in Islamic law and positive law, there are no rules that explain the husband's obligation to wait for the wife's iddah period when he wants to carry out a marriage with another woman. So the issuance of this circular letter will certainly have a positive impact and benefits for women who are undergoing the iddah period and will have time to improve their households. However, on the other hand, if these rules are not implemented properly, it is feared that hidden polygamy will occur by the husband. In this case, to dig deeper into this research, the author used a qualitative descriptive method so that the author conducted research directly in the field with several related sources.